Transição agroecológica em assentamentos rurais no entorno da reserva biológica de Poço das Antas - RJ - Rivetti, Leonardo Vicente (2013)
This study aimed to analyze the process of agroecological transition in Microregion of the São João River Basin, in the state of Rio de Janeiro, more specifically in agrarian reform settlements surrounding the Biological Reserve Poço das Antas. The idea to start a transition process in local agriculture started from the initiative of some technical extension of municipal and nongovernmental organizations, entities technical assistance and rural extension, and farmers and social movements in the region. Introducing aspects of qualitative and quantitative, the research was conducted from realization semistructured interviews to collect information about the object of study, as well as documentary research for gathering data, photographic records and field observations. The dialogue with settled families and technical extension was the main tool to analyze the transition process in field level, identifying and understanding different times of the trajectory of change in the context local agriculture. The adoption of ecological practices in production systems brought improvements in the quality of soil and water properties in favored local biome with the increase in biodiversity and polycultures and agroflorestry systems, diversification of production and improved income for a group of producers. However, despite positive externalities, in current phase, in year 2012, the process of agroecological transition has entered a phase of disjointed in the current phase, with lower capacity range, compared to other times considered in this study. The research points to the importance of new and different theoretical discussion, including policy, around the principles of agroecology in its complexity, to promote a transition in agriculture an appropriate proposal to agriculture in context of human communities and ecosystems they inhabit.